Microencapsulation of red ginger oleoresin in maltodextrin and carrageenan using spray drying - Jayanudin Jayanudin; Retno Sulistyo Dhamar Lestari; Aldi Fathurohman; Seta Dewo (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study was to determine the encapsulation efficiency and cumulative release of red ginger oleoresin from microcapsules with different wall materials. Red ginger oleoresin was added to the maltodextrin solution, followed by a tween 80. The mixture formed was transferred to a spray dryer for the drying process. Other materials used are carrageenan and a combination of maltodextrin and carrageenan in a ratio of 1:1, 2:1, and 1:2. Red ginger oleoresin microcapsules were analyzed for encapsulation efficiency and release test using phosphate buffer medium pH 7.4, then determine release kinetics using zero-order, first-order, Higuchi model, Korsmeyer-Peppas model, and Peppas-Shalin model. The highest encapsulation efficiency was 78.6%, and the lowest cumulative was 58.46% from microcapsules with a wall material of a mixture of maltodextrin and carrageenan with a ratio of 1:2. The release kinetics best fit the Korsmeyer-Peppas and Peppas-Shalin models with anomalous transport (non-Fickian) and Fickian diffusion release mechanisms. Tujuan penelitian ini adalah menentukan efisiensi enkapsulasi dan kumulatif rilis oleoresin jahe merah dari mikrokapsul dengan bahan dinding yang berbeda-beda. Oleoresin jahe merah ditambahkan ke larutan maltodektrin dilanjutkan denganpenambahan tween 80. Campuran yang terbentuk dialirkan ke spray dryer untuk proses pengeringan. Bahan lain yang digunakan adalah karagenan dan perpaduan maltodektrin dan karagenan dengan rasio 1:1, 2:1, dan 1:2. Mikrokapsul oleoresin jahe merah dianalisis untuk efisiensi enkapsulasi dan uji rilis menggunakan medium buffer fosfat pH 7.4, kemudian menentukan kinetika rilis menggunakan model order nol, order pertama, model Higuchi, model Korsmeyer-Peppas, dan Peppas-Shalin. Efisiensi enkapsulasi tertinggi sebesar 78.6% dan kumulatif terendah sebesar 58.46% dari mikrokapsul dengan bahan dinding perpaduan maltodektrin dan karagenan dengan rasio 1:2. Kinetika rilis dengan fitting terbaik dari model Korsmeyer-Peppas dan Peppas-Shalin dengan mekanisme rilis anomalous (non-Fickian) transport dan Fickian diffusion.